STRATEGY FOR UTILIZING THE GAME-BASED LEARNING METHOD BALL-SHAKE IN BAR CHART LEARNING IN INDONESIAN LANGUAGE SUBJECT CLASS II-A SD ISLAM KAUMAN PATI - Unida Estiyowanti, Ulif; Kusmawati, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to identify the steps of the strategy for utilizing the Game-Based Learning (GBL) method ball-shake, as well as the supporting and inhibiting factors in learning bar charts in the Indonesian language subject. This research uses a qualitative approach with a field research type. The research was conducted in class II-A of SD Islam Kauman Pati for approximately 3 months. Data collection techniques were carried out through structured interviews, non-participant observation, and documentation. Data triangulation from informants as well as primary data consists of interviews with the principal, teacher, and students. Meanwhile, secondary data comes from non-participant observation and research documentation at the school. Data analysis using the Miles and Huberman model includes data collection, data reduction, data display, and conclusion drawing. The research results show that 1) the steps of the strategy for utilizing the GBL method ball-shake include learning planning, preparing media and game rules, implementation of the ball-shake game, data processing and bar chart creation, as well as reflection and evaluation of the learning. 2) Supporting factors in the implementation of the GBL method include support from the school, the student activity and enthusiasm, and the use of simple learning media. In addition, the inhibiting factors include limited learning time and an unconducive classroom atmosphere.